2022
DOI: 10.3390/cancers14235981
|View full text |Cite
|
Sign up to set email alerts
|

The Mutually Mediated Chloride Intracellular Channel Protein 1 (CLIC1) Relationship between Malignant Cells and Tumor Blood Vessel Endothelium Exhibits a Significant Impact on Tumor Angiogenesis, Progression, and Metastasis in Clear Cell Renal Cell Carcinoma (ccRCC)

Abstract: Background: Overexpression of chloride intracellular channel protein 1 (CLIC1) in tumor cells has been confirmed, but it has received less attention in the tumor blood vessel endothelium. Aim. The assessment of CLIC1 expression in ccRCC tumor blood vessels and its relationship with TNM parameters and tumor cell CLIC1 expression. Methods: CLIC1 immunostaining in ccRCC was evaluated in 50 cases in both malignant cells and tumor blood vessels (CLIC1 microvessel density-CLIC1-MVD) and was correlated with TNM stagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Furthermore, CLIC1 expression significantly correlated with metastasis in G3 tumors. In another study, Ferician et al found CLIC1 expression in both ccRCC tumors and tumor vessels endothelium [21]. The authors classified the study group depending on CLIC1 expression in the tumor and in the tumor vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CLIC1 expression significantly correlated with metastasis in G3 tumors. In another study, Ferician et al found CLIC1 expression in both ccRCC tumors and tumor vessels endothelium [21]. The authors classified the study group depending on CLIC1 expression in the tumor and in the tumor vessels.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is also supported Based on previous research, CLIC1 is upregulated in various malignant tumors, and its expression is associated with poor outcomes [19][20][21] . Aberrant CLIC1 expression endows tumor cells with high motility and invasiveness, making it a significant contributor to tumor invasion, metastasis, and angiogenesis [39][40][41] . In our study, we found that CLIC1 plays a critical role in cell-extracellular matrix interactions but differs in that it is a key molecule linking matrix stiffness and glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…During postnatal life, CLIC1 expression in the kidney is present both in renal epithelial cells and stromal vascular endothelial cells. CLIC-1 is retained and overexpressed by cc-RCC tumor cells during malignant transformation, with its expression also observed on the stromal tumor blood vessel endothelium ( 112 ) ( Figure 3A ). Researchers detected isolated CLIC1-positive cells inside the tumor stroma as well as in between tumor cells ( 112 ).…”
Section: Cc-rcc Associated Vasculogenesismentioning
confidence: 99%
“…CLIC-1 is retained and overexpressed by cc-RCC tumor cells during malignant transformation, with its expression also observed on the stromal tumor blood vessel endothelium ( 112 ) ( Figure 3A ). Researchers detected isolated CLIC1-positive cells inside the tumor stroma as well as in between tumor cells ( 112 ). Researchers did not study the involvement of isolated CLIC1-positive stroma cells with endothelial morphology in the local initiation of tumor stroma vasculogenesis.…”
Section: Cc-rcc Associated Vasculogenesismentioning
confidence: 99%